THE ISSUES WITH MODERN ENGLISH TEACHING METHODS IN UNIVERSITIES - Asqarova Komila Ergashevna (American Journals, 2024)
The issues with different approaches to teaching foreign languages in universities are discussed in the essay. The direct method, grammar-translation, audiovisual, audio-lingual, and communicative approaches all received special attention. Modern teaching methods, according to the author, involve the application of such a system of procedures, which are intended to help trainees master knowledge independently through active cognitive activity rather than to replicate the teacher's ready-made knowledge presentations.
Keywords: Activities, audiovisual, audio-lingual, communicative, communication, development, direct, education, English, foreign, language, method, modern, process, skill, system, teaching